The Perceived Stress Reactivity Scale for Adolescent Athletes: Translation, Validity and Reliability Study - Ender Şenel; Mevlüt Yıldız; Nazmi Bayköse (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThis study aims to analyze the validity and reliability of The Perceived Stress Reactivity Scale for Adolescent Athletes. 220 athletes including 111 females and 109 males from seventeen different sports branches participated in the study. The age mean of the participants was found to be 19.76±1.05. The sporting age mean was found to be 7.11±2.96. Data was collected by using The Perceived Stress Reactivity Scale for Adolescent Athletes (8), Perceived Stress Scale (9, 11). The factor structure was analyzed by using Confirmatory Factor Analysis in AMOS. Pearson Correlation test was used to analyze factor-factor relationship and criterion-related validity. The method of translation-back translation was used for the translation of the scale into Turkish. The results of the factor analysis displayed that 5-factor model had acceptable fit indices (CFI=.83, SRMR=.07, RMSEA=.07). The 5-factor scale including the subscales of prolonged reactivity, reactivity to work overload, reactivity to social conflict, reactivity to social evaluation, and reactivity to failure had the same factor structure in Turkish athletes. Consequently, it can be said that The Turkish form of the Perceived Stress Reactivity Scale for Adolescent Athletes is valid and reliable.